Assessment of Interpersonal Communication Skills Among Emergency Medical Professionals in Pune, India - Parag Rishipathak; Monesh Bhandari; Anand Hinduja; Meenal Kulkarni (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Effective interpersonal communication is one of the most important skills for healthcare providers to master, in order to deliver high quality patient care. Doctors need to communicate with a wide range of people including peers, administration staff, patients, their family members and caregivers. Of course, the most significant is doctor-patient communication as it forms the foundation of the healthcare delivery system.Poor inter-personal communication skills can jeopardize the patient care process and hence it is expected that healthcare professionals undergo formal training both as part of their medical curriculum and on the job Continued Medical Education. Studies have shown that effective interpersonal communication skills help improve overall healthcare outcomes especially while managing difficult encounters and breaking bad news.Designing training programs with contemporary relevance requires regular needs assessment. It is essential to evaluate the baseline levels of inter-personal communication skills amongst practicing professionals to devise appropriate training strategies.Objective: To assess inter-personal communication skills among Emergency Medical Professionals in Pune.Methodology: The study was conducted among 140 Emergency Medical Professionals (EMPs) employed in various hospitals in the city of Pune, India. A questionnaire tool designed in 2019 by Piyush Ranjan et al was utilized to assess inter-personal communication skills among Emergency Medical Professionals.The tool was administered through online mode. The respondents were given one-day deadline to revert with responses. Any queries pertaining to the questionnaire were clarified during data collection. 131 respondents reverted with completely filled questionnaire. Conclusion: It relies on self-assessment to assess interpersonal communication skills and has a limited sample size. Yet, the study is an eye-opener to the incidents of conflicts in emergency healthcare settings and the barriers that prevent a healthy doctor patient relationship